Kajian Komparatif Parameter Ekonomi (Harga Susu dan Pakan) Terhadap Efisiensi Penggunaan Teknologi Pakan Pada Usaha Sapi Perah - Bayu Setya Hertanto (Universitas Sebelas Maret (UNS), 2014)
The objective of the study was to evaluate the impact of feed technology on changing of milk and feed price, and also its impact on efficiency of feed technology in dairy farm. In this study, fifteen lactating dairy cows were divided into 3 groups based on the feed technology. Production parameters measured were milk production and quality for 42 days, while economic parameters were milk and feed price. The highest milk production was produced by feed technology III which was Rp. 11,845 l/herd/day. The highest milk quality was resulted in by feed technology II with quality standard of fat 3.960%, SNF 8.312%, TS 12.272%, and milk density 1.029. Result showed that the lowest was by feed technology III, which was Rp. 1,143.80/l. Income Over Feed Cost (IOFC) showed that the use of feed technology III was more efficient than other feed technologies, which was Rp. 24,664.55/herd/day with the milk price of Rp. 4,207.55/l.Key words: Feed technology, milk production, milk quality, milk price, feed price